2018
DOI: 10.7752/jpes.2018.s4286
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: According to the purpose of the study, in the process of physical education, indicators of physical development, functional state, level of physical working capacity, basic motor qualities, morbidity by the main classes of diseases were investigated and analysed. Analysis of the average statistical indicators of physical development, in particular length and body weight, girth dimensions meet the age standards. We found that 25.0 % (n = 39) of young men have a body mass deficit, in 17.3 % (n = 27) of young men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 9 publications
4
7
0
3
Order By: Relevance
“…In the study of indicators of physical development, we found that in the younger school age, the high variability of the body mass index, which indicates the process of forming of the basic anthropometric characteristics. The results of our studies are confirmed in the works of (Biletska, 2006;Kozhokar, 2018;, who points out that the primary school age in terms of changing somatotypes, the rate of increase of body length and body weight is heterogeneous. In the age range from 7 to 9 years, deep and extremely ambiguous rearrangements take place.…”
Section: Discussionsupporting
confidence: 88%
“…In the study of indicators of physical development, we found that in the younger school age, the high variability of the body mass index, which indicates the process of forming of the basic anthropometric characteristics. The results of our studies are confirmed in the works of (Biletska, 2006;Kozhokar, 2018;, who points out that the primary school age in terms of changing somatotypes, the rate of increase of body length and body weight is heterogeneous. In the age range from 7 to 9 years, deep and extremely ambiguous rearrangements take place.…”
Section: Discussionsupporting
confidence: 88%
“…Many researchers (Balamutova, 2011;Kozhokar, 2018) consider that a decrease in the adaptive capabilities and the energy potential of the students is connected with a low level of physical condition, which is identified as a complex of morphological, physical and functional indicators of the development and status of the body.…”
Section: Introductionmentioning
confidence: 99%
“…Specialists in the field of physical culture and sports carry out an intensive search for new directions, forms and methods of mass sports work with pupils which meet modern requirements and can solve a complex of important tasks facing the school education system Pityn, 2017;Melnyk, 2017;Kozhokar, 2018).…”
Section: Discussionmentioning
confidence: 99%